Sams teach youself Python programming for Raspberry Pi in 24 hours - Blum, Richard, 1962-; Bresnahan, Christine (2014)
The Raspberry Pi has taken the world by storm. A cheap and tiny device, it is a full-fledged PC that's already being used in home automation, robotics, home theatre and a world of other applications. 'SAMS Teach Yourself Raspberry Pi Programming in 24 Hours' guides you through every step of learning Python programming on Raspberry Pi, and gives you a springboard for creative projects on this immensely popular new platform.
Includes index.
Keywords: Raspberry Pi (Computer) -- Programming; Python (Computer program language); Digital Lifestyle